The Effectiveness of Hanzhala and Watermelon Icons as A Symbol Representation of The Palestine Struggle on The Palestine-Israel Conflict - Lesmana, Maman (LPPM IAIN Parepare, 2024)
The never-ending conflict between Palestine and Israel has resulted in great suffering to this day. However, the fighting spirit of the Palestinian people continues to grow strong roots. Palestinian people use various media to voice their rights and criticize the current situation affecting Palestine, one of which is in the form of caricature art. Naji Al-Ali, as a caricature artist, is active in voicing criticism and the conditions of concern faced by Palestinian society. Hanzhala is one of Naji's works created against the backdrop of the Nakba. Hanzhala then evolved into a symbol of resistance and a strong symbol of struggle for the national identity of the Palestinian people. This research will analyze the relevance and effectiveness of the use of Hanzhala caricatures as a reflection of the factual conditions of Palestinian resistance in the Palestinian-Israeli conflict from 7 October 2023 until now. This research was researched using a descriptive qualitative approach method through relevant library sources. Based on the research analysis that has been carried out, the Hanzhala caricatures by Naji al-Ali remain relevant in depicting criticism and current conflict situations. However, the use of Hanzhala caricatures as a medium for criticism has not attracted much attention from the global community, so the aim of using caricatures as a medium to increase recognition of the resistance to the Palestinian struggle is less effective.